2011
DOI: 10.1161/atvbaha.110.211789
|View full text |Cite
|
Sign up to set email alerts
|

The Bilirubin-Increasing Drug Atazanavir Improves Endothelial Function in Patients With Type 2 Diabetes Mellitus

Abstract: Objective-In type 2 diabetes mellitus (T2DM), oxidative stress gives rise to endothelial dysfunction. Bilirubin, a powerful endogenous antioxidant, significantly attenuates endothelial dysfunction in preclinical experiments. The Gilbert syndrome is accompanied by a mild and lifelong hyperbilirubinemia and associated with only one third of the usual cardiovascular mortality risk. The hyperbilirubinemia caused by atazanavir treatment closely resembles the Gilbert syndrome. We thus hypothesized that treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
99
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 41 publications
4
99
1
Order By: Relevance
“…35 Dekker et al 36 have shown that an increased level of bilirubin induced by atazanavir improves endothelium-dependent vasodilation in patients with type 2 diabetes mellitus, supporting our findings. However, in contrast, Dubé et al 37 found no change in endothelial function in healthy subjects treated with atazanavir despite an increase in bilirubin level.…”
Section: Discussionsupporting
confidence: 89%
“…35 Dekker et al 36 have shown that an increased level of bilirubin induced by atazanavir improves endothelium-dependent vasodilation in patients with type 2 diabetes mellitus, supporting our findings. However, in contrast, Dubé et al 37 found no change in endothelial function in healthy subjects treated with atazanavir despite an increase in bilirubin level.…”
Section: Discussionsupporting
confidence: 89%
“…HO-1 degrades heme to form biliverdin, CO, and Fe 2+ ; the former is further converted into unconjugated bilirubin. Bilirubin is increasingly recognized to be vasoprotective in cardiometabolic diseases (18,20), and the total plasma bilirubin concentration is lower in diabetic patients (17). The current study also shows a reduced serum level of unconjugated bilirubin in db/db mice, which is increased after 2 weeks of hemin treatment.…”
Section: Discussionsupporting
confidence: 62%
“…Bilirubin is a potent antioxidant, and efforts have been directed to determine whether bilirubin can be used to treat diseases associated with oxidative stress. Indeed, atazanavir, a drug that raises unconjugated bilirubin levels, enhances plasma antioxidant capacity and improves EDRs in diabetic patients (20).…”
mentioning
confidence: 99%
“…Atazanavir has even been tested in HIV‐negative diabetic patients to determine its effect on carotid intimal thickness. In one of these trials, endothelial function improved,16 whereas the second study showed only a reduction in low‐density lipoprotein levels and blood pressure 17. To potentially explain these mixed findings, atazanavir and other protease inhibitors have been shown to actually increase endothelial dysfunction, oxidative stress, and von Willebrand factor, thereby counteracting some of the benefits of the elevated bilirubin levels 46, 47, 48.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the antiretroviral drug atazanavir can competitively inhibit uridine diphosphate glucuronosyltransferase 1A1, leading to an increase in unconjugated bilirubinemia 15. Several studies have shown atazanavir use can improve endothelial function and reduce lipid levels and blood pressure in HIV‐uninfected diabetic patients 16, 17. Among HIV‐positive individuals, atazanavir decreased markers of inflammation and slowed progression of carotid intimal‐medial thickness when compared with other antiretroviral treatment (ART), an effect that appears to be partially mediated by bilirubin 18, 19…”
mentioning
confidence: 99%